Stabilization of lateritic soil using cement and lime for road construction - Htet Okkar Kyaw; Nyan Myint Kyaw (Innovation in Engineering, 2025)
In developing countries, crushed rocks are mainly used in road subbase and base courses for road construction. As a result of extremely high fuel prices and lengthy travel times, particularly from Mokepalin, which is 92 miles from Yangon, the exorbitant costs of crushed rock aggregates for road building in Myanmar have therefore become a major concern. Due to energy consumption and carbon emissions, this dependence on remote sources results in increased building costs, project delays, and environmental destruction. In Yangon, local marginal materials (lateritic soil) are also available in Hmawbi, Hlegu, Taikkyi and Twantay townships. According to the engineering properties of soil in term of CBR, Hmawbi lateritic soil is nearly the same as the Mokepalin. Therefore, lateritic soil from Hmawbi was selected as a case study material for this research in order to reduce costs and to be more economical. To evaluate the engineering properties of soil, laboratory tests including sieve analysis, Atterberg limits, UCS, compaction, and CBR testing were carried out. The purpose of this paper is to stabilize lateritic soils for possible use as materials for road sub base and base to substitute crushed rocks. Results showed that 2% of cement and lime content met subbase course for Unconfined Compressive Strength (UCS) values of 0.75 MPa and 1.75 MPa according to Joint Departments of the Army and Air Force and 16% of cement satisfied for road base course for UCS value of 5.36 MPa. The use soil lime mixture was found to be unsuitable for road base course. Cement stabilized lateritic soil proved to be stronger, durable and better than soil lime mixture for road construction.